A review on the effects of physical built environment attributes on enhancing walking and cycling activity levels within residential neighborhoods. (February 2016) - Wang, Y.; Chau, C.K.; Ng, W.Y.; Leung, T.M.
Abstract: The growing worldwide awareness of the significant impacts of physical activities on physical and physiological health has aroused great interest in the role of the physical built environment plays in walking and cycling activities. This comprehensive review shows how specific details of the built environment enhance people's walking and cycling. This was accomplished through identifying the barriers to walking and cycling activities as well as the general and specific characteristics of the major physical built environment attributes within a residential neighborhood that can help overcome these barriers and enhance the walking and cycling activity levels. Also the effectiveness of some individual attributes was also compared. Of particular value of this study is that its structure and level of details of information laid out in this review can facilitate building designers and neighborhood planners in creating a supportive environment within residential neighborhoods. Highlights: Review provided on which built environment could enhance walking and cycling levels Major physical built environment related barriers to walking and cycling were identified Characteristics of built environment attributes within neighborhoods were identified for enhancing walking and cycling levels The effectiveness of the individual physical built environment attributes were compared